EFFECT OF GARLIC (ALLI UM SA TI VUM) ON BLOOD PRESSURE IN HEALTHY VOLUNTEERS - Makki; Zuhair A; Haider Al-wa; Shaheen; Ayad Al (Basrah Journal of Veterinary Research)
The study was conducted on two groups of individuals. Group A (treatment) consisted of l0 healthy volunteers who were administrated garlic (Allium sativum) for thirty days and then followed for another 30 days without garlic. Group B(control) ll healthy subjects served as a control. Garlic ingestion signiﬁcantly lowered (p0.05) in systolic B. Pr. on male, female and total. Significantly lowered (p